Communication Technology: Tool for Changing the Face of Worship in Christian Religion in Nigeria - Ajani, Olanrewaju Tunde; Adeyemi, Adebola Rachael (NIU Journal of Humanities, 2019)
Information and communication technology has come to stay and its influence has percolated into every fiber of the society, religion inclusive. Religion being what it is, is always reluctant to embrace change especially when it comes to what has to do with science and technology. However, it seems religion has made an exception with ICT, religious centers has embraced ICT with a remarkable open arms. Though its potential to further the propagation of religion in the country has greatly been harnessed, also it has led to some religious malady. Therefore this paper examined the introduction of ICT into Religion in Nigeria. This research work further point out the importance of the ICT to religion. This paper also investigates the effects of ICT on Religion in Nigeria. In carrying out the research, qualitative method was used and relevant materials were consulted for text analysis. Few recommendations were made which include; religion should draw a line in religious worship that ICT must not cross, so that it (ICT) may not be tempted to hijack the spiritual essence of worship. Keywords: Religion, technology, worship and Information